(untitled) (Annals of Medical Research, 2022)
Aim: Our aim in this study was to determine early cochlear changes caused by hypoxia and snoring noise in patients with Obstructive sleep apnea Syndrome and to examine the relationship of these changes with polysomnography parameters. Materials and Methods: A total of 149 patients with symptoms of snoring and sleep apnea who underwent polysomnography were included in this study. We formed a patient and control group based on the apnea-hypopnea index. We compared the audiometric parameters and the Distortion Product Otoacoustic Emission amplitudes of the groups. We evaluated Polysomnography parameters such as snoring number, snoring index, oxygen desaturation index, minimum pO2, mean pO2, pO2 ≤88%, which affect these results, by correlation. Results: High frequency audiometry and high frequency Distortion Product Otoacoustic Emission amplitudes showed statistically significant differences in the Obstructive Sleep Apnea Syndrome group compared to the control group (p<0.001). PO2 ≤88% affected high frequency audiometry and mean pO2 affected high frequency Distortion Product Otoacoustic Emission amplitudes more than snoring number and snoring index. (p<0.001). Conclusion: İn patients with OSAS, the inner ear is affected by hypoxia and snoring. However, the effect of hypoxia on cochlear dysfunction is greater than snoring noise. High-frequency audiometry and Distortion Product Otoacoustic Emission can guide in the early period to determine cochlear damage.